The Design of Unit-Lesson Reflection Model For Senior High School English Teachers - Makasau, Rosmayasinta (Jurnal Masalah Pastoral, 2018)
Each of us in our professional lives as a teacher is likely to face different kind of events or incidents during teaching and learning process in the classroom. The situation in the classroom is sometimes unpredictable. The teachers are expected to be proactive and decide wisely to respons any unpredictable situations. They need to reflect on what happened, describe the events and identify the possible causes of the unexpected events. Then, teachers may analyse the findings and think of what to do to improve the unexpected events to be applied in the future actions. This study purposed to help teachers to evaluate such unexpected events occured in order to plan a new action if it is occured in the future time. So, the writer designed and provided a simple and efficient model of pedagogical practice reflection for senior high school teachers. Questionnaires and interview were contributed to gain feedback from the English teachers (as the participants in this study) related to the proposed design of unit-lesson reflection model. The library study was also conducted to generate theories in this issue.